Genetic variability and trait association in maize (Zea mays L.) varieties for growth and yield traits. Issue 9 (September 2021) - Magar, Bigul Thapa; Acharya, Subash; Gyawali, Bibek; Timilsena, Kiran; Upadhayaya, Jharana; Shrestha, Jiban
Abstract: The present study was carried out to study the variation, broad-sense heritability, genetic advance, correlation among traits for growth, yield, and its attributing traits in maize genotypes. Ten maize genotypes were evaluated in a randomized complete block design (RCBD) with three replications from June 2019 to September 2019. The results indicated that the genotypes were significantly different for all traits. For all traits, the phenotypic coefficient of variation (PCV) was higher than the genotypic coefficient of variation (GCV). The grain yield showed the highest PCV (26.91%) and GCV (25.9%) whereas leaf width at maturity showed the lowest PCV (4.07%) and GCV (6.05%). Genetic Advance over Mean (GAM) for the traits ranged from the lowest value (0.1%) for days to 50% anthesis to the highest value (51.36%) for grain yield. Higher values of heritability and GAM % were obtained for grain yield (0.93, 51.36%) and 1000 grain weight (0.99, 36.95%) whereas the lowest values of heritability and GAM% were found for leaf length (0.5, 7.25%) and leaf width (0.39, 5.25%). Grain yield showed positive and significant phenotypic correlation with test weight (r = 0.706), cob length (r = 0.671), cob diameter (r = 0.573) and number of rows per cob (r = 0.539), respectively. Therefore, traits having high variation can be used as selection indices for indirect selection for the improvement of maize productivity. Abstract : Maize, PCV, GCV, Heritability, Genetic advance, Correlation